2019
DOI: 10.1111/jdi.13176
|View full text |Cite
|
Sign up to set email alerts
|

Family history of diabetes in both parents is strongly associated with impaired residual β‐cell function in Japanese type 2 diabetes patients

Abstract: Aims/Introduction: The objective of the present study was to clarify the association of the type and number of first-degree family history of diabetes (FHD) with the clinical characteristics, especially with residual b-cell function, in type 2 diabetes patients. Materials and Methods: A total of 1,131 type 2 diabetes patients were recruited and divided into four groups according to FHD information as follows: (i) patients without FHD (FHD-); (ii) those with at least one sibling who had diabetes without parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“… 31 35–37 Our study showed that the patients with a parental history of diabetes were younger than those with no parental history of diabetes, which was consistent with several published studies. 14 38 Currently, whether genetic predisposition or lifestyle transformation is responsible for early disease onset in those with a parental history of diabetes is controversial. Alternatively, the improved awareness of diabetic symptoms of those patients could be explained by early disease onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 31 35–37 Our study showed that the patients with a parental history of diabetes were younger than those with no parental history of diabetes, which was consistent with several published studies. 14 38 Currently, whether genetic predisposition or lifestyle transformation is responsible for early disease onset in those with a parental history of diabetes is controversial. Alternatively, the improved awareness of diabetic symptoms of those patients could be explained by early disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have found that an FHD also plays an important role in residual β-cell function, but the results remain controversial. [14][15][16] On the one hand, one study demonstrated that patients with an FHD had significantly lower levels of C-peptide than those without an FHD. 15 On the other hand, another study reported that the impact of an FHD on the C-peptide level was definitely weak.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…New gene regions involved in type 2 diabetes in East Asian individuals have been identified 6 , and a family history of diabetes also has a substantial influence on the pathophysiology of diabetes. Iwata et al 7 . evaluated the relationships of the number and type of family history of diabetes with β‐cell function, estimated using fasting C‐peptide concentration and the C‐peptide index (calculated using the formula: 100 × fasting C‐peptide concentration / plasma glucose concentration) in Japanese patients with type 2 diabetes.…”
Section: Samples Evaluation Methods Non‐diabetes Diabetes Reference N...mentioning
confidence: 99%
“…A family history of type 2 diabetes (FHT2D) is a well-known strong risk factor for the onset of diabetes 9 and is therefore included in many diabetes predictive models 10 . Of note, this phenomenon is dependent on the hereditary diabetic disease burden, so a FHT2D in both parents is more strongly associated with an impaired residual β-cell function 11 13 . Several studies in subjects with obesity demonstrated that a FHT2D accelerates the development of atherosclerosis among diabetes-free subjects.…”
Section: Introductionmentioning
confidence: 99%